Respuesta :
I would subtract the 2nd from the first one
so -4x - -2x = -2x
4y - 4y = 0
-20 - -2 = -18
-2x = -18
now I would divide that by -2 to get the value for x
so no we have x = 9
now you just have to substitute that into one of the equations and simplify to get y
-2 X 9 + 4y = -2
-18 + 4y = -2
4y =16
y = 4
For addition:
-4x+4y=-20 (multiply by -1) to get 4x-4y=20
-2x+4y=-2 (Leave as it is) to get -2x+4y=-2
Add together to eliminate the y term
Solve for x (x=9)
Plug in x to either equation to get y (y=4)
Answer: (9,4)
For subtraction:
-4x+4y=-20
-2x+4y=-2
Since the equations are already ready for elimination by subtraction, just Subtract to eliminate the y term
Solve for x (x=9)
Plug in x to either equation to get y (y=4)
Answer: (9,4)
-4x+4y=-20 (multiply by -1) to get 4x-4y=20
-2x+4y=-2 (Leave as it is) to get -2x+4y=-2
Add together to eliminate the y term
Solve for x (x=9)
Plug in x to either equation to get y (y=4)
Answer: (9,4)
For subtraction:
-4x+4y=-20
-2x+4y=-2
Since the equations are already ready for elimination by subtraction, just Subtract to eliminate the y term
Solve for x (x=9)
Plug in x to either equation to get y (y=4)
Answer: (9,4)